Her fear [large type] - Gray, Shelley Shepard (Gray, Shelley Shepard. Amish of Hart County, 2018)
"In New York Times bestselling author Shelley Shepard Gray's novel of suspense in her Amish of Hart County series, an EMT falls for a woman with ties to an Amish community where people are dying similar, suspicious deaths"--